Memories of George Barton - Finlayson, Christopher F (Victoria University of Wellington Law Review, 2012)
This address was given by the Attorney-General, the Hon Christopher Finlayson, at the special sitting of the High Court in Wellington to honour Dr George Barton QC on Wednesday 6 July 2011.